Validity and Reliability Study of Science-Edutainment Interactive Multimedia on Earth Topic for the 7th Graders of Junior High Schools - Mahmudah Mahmudah; Munzil Munzil; Erni Yulianti (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
Natural science, as a fundamental science, requires a series of observations to be understood. For the subject about structure of earth, earthquake, and volcano, the students need the direct observation because the nature of the subject that tends to be abstract. In order for the students to be able to observe directly about the subject of earth that tends to be formed in an abstract concept, therefore the students need the learning media that is able to change that concept into the concrete one moreover also can change it into a fun education for the students. The media that is able to solidify the abstract concept is a media in a form of interactive multimedia. In order to make the students become ecstatic during the learning process, it is a need to do the edutainment approach. Therefore, it is a necessary to do an observation with a purpose to produce the product in a form of interactive multimedia named science edutainment with the topic of earth that is applicable and valid for seventh grade of junior high school students. This research used 4D method without dissemination step. The applicability of the developed product is obtained from the validation of product and the readability test. According to the results of media validation done by the expert, the media was considered appropriate by the percentages of 76.4% for media appropriateness and 88.5% for content appropriateness. On legibility test, it obtained 91.3% by teachers and 93.5% by students, which mean that the media was very appropriate. Hence, the interactive multimedia of science-edutainment on earth topic for the 7th graders of Junior High Schools is considered appropriate and valid.